Karnataka mandal panchayats finances: Imbalance in needs and resources - Devendra Babu, M. (1996)
Despite success in implementation of decentralised system between 1987-92 and tremendous impact of Mandal Panchayats at the village level, the Mandal Panchayats failed to do much in certain important areas due to lack of resources. The author, therefore, examines the patterns of revenue and expenditure of Mandal Panchayats, their problems and remedial measures to facilitate understanding of such problems which Gram Panchayats in all probability may face in future, according to the author. - Reproduced
Keywords: Panchayat - India - Karnataka; Panchayat